PENGARUH KONFLIK PERAN TERHADAP KINERJA KARYAWAN MELALUI STRAIN SEBAGAI VARIABEL INTERVENING PADA KARYAWAN PT. POS INDONESIA KABUPATEN PAMEKASAN - SILVI DWI YANTI, SEPTIANA; BUDIONO (Jurnal Ilmu Manajemen (JIM), 2018)
AbstractThis study aimed to examine the independent variable (role conflict) on employee performance through strain as intervening variable on the employee of PT. Pos Indonesia in Pamekasan district. Data were obtained from giving questionnaire and making interview. The sample that were used in this study were 55 respondents. That were taken by saturated sampling method. Data collection techniques used is a questionnaire technique that is distributed directly to respondents at PT. Pos Indonesia. Analysis statistics that was used was partial least square (PLS). This study used validity test technique and reability test. The results of this study indicate Role Conflicts have a negative and significant impact on Employee Performance, role conflict has a positive and significant impact on Strain, Strain has a negative and significant effect on Employee Performance, while the Strain not able to mediate from the influence of role conflict against employee performance.Keywords: Role conflict, strain, employee performance